2018
DOI: 10.14689/ejer.2018.73.3
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Responses to CL-Based Teaching of English Prepositions

Abstract: Purpose: Most EFL textbooks suggest the use of vivid pictures and verbal explanations in teaching English prepositions. However, this word class appears in collocations, and rote-learning does not really help learners retain and use this word class successfully. Cognitive linguistics (CL) has implications for English language teaching as it rests against the relationship between the human mind and language. Several experimental studies have aimed to investigate the effects of CL-based treatment on learners' re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…Their results indicate that the major effect of second language learning context, supported by the 3D images and symbols in VLE, accounts for the success of students who learn Chinese vocabulary in SL. Moreover, as reported by Hung et al [27], the visual 3D nature of SL can be helpful for English learners to differentiate prepositions such as "under", "above", "in", "out" etc., when describing and locating objects in space. Other studies have also confirmed that SL effectively supports language acquisition by building an immersive learning environment that helps learners easily visualize the learning contents.…”
Section: Language Training In Sl Vlementioning
confidence: 87%
“…Their results indicate that the major effect of second language learning context, supported by the 3D images and symbols in VLE, accounts for the success of students who learn Chinese vocabulary in SL. Moreover, as reported by Hung et al [27], the visual 3D nature of SL can be helpful for English learners to differentiate prepositions such as "under", "above", "in", "out" etc., when describing and locating objects in space. Other studies have also confirmed that SL effectively supports language acquisition by building an immersive learning environment that helps learners easily visualize the learning contents.…”
Section: Language Training In Sl Vlementioning
confidence: 87%
“…According to Hung et al (2018), in traditional classrooms, the teacher's role was to be an expert giving lectures to learners who are considered empty minds that need filling. With the advance of Web 2.0 and social networks, learners have many media channels at their disposal to present their own ideas.…”
Section: The Role Of the Learner And The Teacher In Mobile Learningmentioning
confidence: 99%
“…Only some of the studies focus on the major lexical categories (Giang & Khuong, 2014;Borovsky & Elman, 2006;Netra, 2016), L2 word order processing (Erdocia & Laka, 2018;Lee, Lu, & Garnsey, 2013;McDonald, 2008;Cat, Klepousniotou, & Baayen, 2015), language skills (Tare & Gelman, 2010;Burchinal, et al, 2000), teaching grammar (Raflis & Lase, 2018;Tian, 2015;Kermer, 2016), but not for a minor lexical group of words such as prepositions or particles. Few cognitive analyses of preposition have been studied so far; However, the field of these researches are mainly focused on language teaching (Wijaya & Ong, 2018;Hung, Vien, & Vu, 2018). That is why the research gap for conceptual transfer is open up at present.…”
Section: Literature Reviewmentioning
confidence: 99%